Do extracurricular activities contribute to better adolescent outcomes? A fixed-effects panel data approach - O'Flaherty, Martin; Baxter, Janeen; Campbell, Alice (My University, 2022)
Extracurricular activity participation is associated with positive academic, health, and behavioral outcomes for adolescents, but these findings may reflect unobserved confounding rather than participation effects. Data were drawn from 3885 adolescents aged 12-15 in a nationally representative cohort of Australian adolescents. Effects of participation in three kinds of extracurricular activity (team sport, individual sport, and arts) on an array of outcomes were modeled using fixed-effects regression to account for potential unobserved confounding. Strong bivariate relationships between all forms of activity participation and positive adolescent outcomes were found. These associations were much smaller in the fixed-effects analysis, but beneficial effects of sports for mental health and arts for peer group characteristics remained statistically significant. Minimal effects of extracurricular activity participation for academic achievement were found. Extracurricular activity participation has beneficial effects on adolescents' mental health and exposure to peers' delinquent behavior.
Journal of Adolescence
Keywords: Adolescents and youth; Health and wellbeing; Learning, education and training